Penerapan Digital Marketing dalam Mendukung Kegiatan Pemasaran Pada Usaha Taniku Cirebon - Otto Fajarianto; Siti Jubaedah; Dedet Erawati (Janaka, Jurnal Pengabdian Masyarakat, 2021)
Small and Medium Enterprises have a large enough role for the welfare of the community. This sector can absorb a large enough workforce and provide opportunities for UMKM to develop and compete with companies. The partner of this activity is UMKM Taniku which is engaged in the agricultural sector of Cirebon whose business activities are selling and providing services. The problems faced by Taniku are the marketing of products and services, productivity, and a decrease in turnover. Implementation methods include (1) analyzing the situation and identifying partner problems, (3) determining partner problem solutions and achievement targets, and (4) evaluating activities. The solution offered is to improve aspects of marketing management that have an impact on increasing productivity and sales turnover by implementing digital marketing applications. Conduct training and marketing assistance by utilizing web-based technology. The results of this activity are expected to (1) increase turnover to increase revenue, (2) increase productivity (3) have a digital catalog of products that attract market share, (4) carry out online promotions through the web or other social media accounts so that products are better known to the public extensivel